O Curinga no teatro Fórum: formação teatral e política pelo bufão - Oliveira, Sarah Reimann (2017)
The Forum Theater is one of the most widespread Theater of the Oppressed’s modalities. It was systematized in the 1970s and it approaches social and psychological opressions on the scene so that they are discussed and restaged by the public. The mediator between the forum-scene and the public is the joker. This work proposes an investigation between the Forum Theater joker’s language and the buffoon. The buffoon is a clown with origins in the medieval times that uses comicality mainly through grotesque body gestures and ironic speech. This research has as primordial objective to investigate political and theatrical buffoon’s characteristics being in Forum Theater’s joker in order to provoque the critical eye. To that end, it was accomplished a historical rescue of the Forum Theater, of the joker and of the buffoon by means of books and videos that bring concepts and practices about them; it was written about the Victor Turner’s social drama bearing in mind one of the research’s development axes: the study of the Cultural Performances and their relations with the Theater of the Oppressed; and it was effected an analysis of videos, found on the internet, about Forum Theater’s plays presented in the brazilian’s state capitals. The selected videos’ analysis was done parting from two categories, they are: Forum theater and jokering; and buffoon aspects. The analyis’ categories were guided through three questions: In what way the Forum Theater has been presenting regarding the criticality matters? Is there criticality in the spect-actors’ fruition through the jokering? Can the buffoons’ aspects contribute to the Forum Theater’s joker formation? The mainly consideration obtained in this investigation shows that part of the studied Forum Theater plays are politically emptied and don’t seek the spect-actor’s critical eye. Therefore is fundamental that the joker builds his/her acting game by the improvisational quality that is one of the atributes of the buffoon’s activities, in this way is going to be possible having criticality in the spect-actors’ fruition.